Kandungan Bahan Organik dan Karakteristik Sedimen di Perairan Betahwalang, Demak - Jamaludin Jamaludin; Sri Sedjati; Endang Supriyantini (Universitas Diponegoro, 2021)
Betahwalang is a coastal village located in Demak Regency. As a village located in a coastal area, the local population mostly relies on the fisheries sector sourced from sea products. Betahwalang Village has a Mangrove Ecosystem, which is included in the tidal river area of Betahwalang Village. This study aims to look at the comparison of organic matter levels in sediments during tidal and receding river water. Sampling in the field was conducted in March 2019. Sediment samples were taken from 5 stations divided into jetty, mangrove, estuary, and beach areas, where each station was repeated 3 times during high tide and low tide. Analysis of organic matter content of sediment samples using gravimetric methods and data analysis using Non-Parametric Kruskal-Wallis H. The results showed the highest levels of sediment organic matter at station 5 were 74.87 ± 1.81% (low tide) and 66.99 ± 0.38% (high tide) and the lowest sediment organic matter content. at station 4 were 31.56 ± 2.14% (low tide) and 26.93 ± 2.51% (high tide). These results indicate that the organic matter content in the sediment at low tide is higher than at high tide with results that are not significantly different (sig = 0.05). Betahwalang adalah desa pesisir yang terletak di Kabupaten Demak. Sebagai desa yang terletak di wilayah pesisir, penduduk setempat sebagian besar mengandalkan sektor perikanan yang bersumber dari hasil laut. Desa Betahwalang memiliki Ekosistem Mangrove yang termasuk dalam wilayah sungai pasang surut di Desa Betahwalang. Tujuan dari penelitian ini adalah untuk melihat kondisi perairan sungai Betahwalang ditinjau dari kandungan bahan organik dalam sedimen selama pasang dan surut. Pengambilan sampel di lapangan dilakukan pada bulan Maret 2019. Sampel sedimen diambil dari 5 stasiun yang dibagi menjadi area dermaga, mangrove, muara dan pantai, di mana setiap stasiun diulang 3 kali selama pasang dan surut. Analisis kandungan bahan organik sampel sedimen menggunakan metode gravimetri, dan analisis data menggunakan Non-Parametrik Kruskal-Wallis H. Hasil penelitian menunjukkan kadar bahan organik sedimen tertinggi di stasiun 5 sebesar 74,87 ± 1,81% (air surut) dan 66,99 ± 0,38 % (air pasang) dan kandungan bahan organik sedimen terendah. di stasiun 4 sebesar 31,56 ± 2,14 % (air surut) dan 26,93 ± 2,51% (air pasang). Hasil ini menunjukkan bahwa kandungan bahan organik dalam sedimen pada saat air surut lebih tinggi daripada saat air pasang dengan hasil yang tidak berbeda nyata (sig=0,05).